Competitive Intelligence for Selected Members of the Aerospace Division in Africa - Camrda, Ondřej; Černý, Jan; Urbánek, Matyáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
The ability to collect, process and exploit vast amount of open data and information in today's fast-paced and globalized business world essentially determines the success or failure of companies in the marketplace. Especially during this time, when aviation is facing an absolutely unprecedented crisis, this statement is more accurate than ever. It is safe to say that Czechoslovak Group, and specifically its Aerospace division, still has a lot to learn in this respect. Therefore, the main objective of this thesis is to use a systematic process of "Competitive Intelligence" to map the critical air traffic management infrastructure in Africa for selected companies of the Aerospace division. Africa offers significant business potential for the suppliers of these advanced technologies, as rapid population growth has still not been reflected in the increase in air traffic and the current state of the infrastructure in many countries is, according to many international organizations, insufficient to ensure the safety of air navigation services. This is mainly due to a lack of qualified professionals in this area and in some countries, a lack of financial resources for investments. The output of this work is a detailed report including dynamic keyword monitoring that can serve as a basis for business users and management of the selected companies in the division to make informed and strategic decision on which specific countries to direct sales and marketing efforts to and with the ultimate goal being the acquisition of new international references. A secondary objective of this work is to describe the technical solution itself, which could serve as a template for future use in other areas of interest or business areas of the Czechoslovak Group.
Vedoucí práce: Jan Černý
Závěrečná práce - Institut celoživotního vzdělávání (MBA)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet